Analisis Tingkat Keragaman Cempedak di Kabupaten Bangka dan Kabupaten Bangka Barat berdasarkan Karakter Morfologi - Meyta Eka Sopiani; Anggraeni Anggraeni; Edi Romdhoni (Department of Biology, Faculty of Agriculture, Fisheries and Biology, University of Bangka Belitung, 2021)
Indonesia is one of central plant genetic diversity in the world, especially for tropical fruits such as Durian, Mangosteen, and Cempedak. Bangka island is one area of the spread of Cempedak in Sumatera. Each plant has a different gene diversity in each tree. Information on the genetic diversity of plant can be known through morphological approaches. Research analyzing the level of diversity based morphological character has never been conducted in Bangka and West Bangka Region. The purpose of this research are to test the level of Cempedak in Bangka Island based on morphology character, so that can bring basic information about the diversity of Cempedak. The location of exploration of this research are in Bangka and West Bangka Region. Determination of sample trees using purposive sampling method. Morphological character parameters are observed in vegetative andgenerative organs which include qualitative and quantative character. Data processing is carried out with reference to UPGMA through the NTSYpc 2.1 program. The result of this research have been founded 6 cultivars of Cempedak, they are Cempedak Kuning, Cempedak Tembaga, Cempedak Nangka, Cempedak Tikus, Cempedak Ular and Cempedak Kapas, they have variative characteristic of leaves, tree, fruit, and seed. The result of similarities analysis of 6 cultivars of Cempedak are 2 main category with 38 % similarities coefficient and 62% differences coefficient. The most diverse morphological character is the shape and size of the leaves, the shape and size of the fruit, the fruit exocarp color, the shape of exocarp surface and the shape of the seeds.